2001
DOI: 10.1093/jxb/52.359.1227
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear fusion leads to chromosome doubling during mannitol pretreatment of barley ( Hordeum vulgare L.) microspores

Abstract: A cytological study of barley microspores during pretreatment of the uninucleate stage to the early culture stage was conducted utilizing six genotypes. Among the three main pretreatments investigated, microspores completed the first mitotic division during 28 d cold pretreatment of spikes, with or without leaf sheath attached, and during 0.3 M mannitol pretreatment of anthers at 25 degrees C. However, during a 4 d pretreatment in 0.3 M mannitol at 4 degrees C this first mitotic division was blocked or delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 26 publications
6
49
2
2
Order By: Relevance
“…A tendency for lower doubling rates was observed after n-butanol treatments, although significant differences were only found in Pavon. Nuclear fusion has been proposed to be the main mechanism of spontaneous doubling in barley (González-Melendi et al 2005;Kasha et al 2001) and maize (Testillano et al 2004) microspore embryogenesis. High frequencies of spontaneous doubling in cereals appear to be induced by treatments that block cell wall formation during the first cell divisions (Shim et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A tendency for lower doubling rates was observed after n-butanol treatments, although significant differences were only found in Pavon. Nuclear fusion has been proposed to be the main mechanism of spontaneous doubling in barley (González-Melendi et al 2005;Kasha et al 2001) and maize (Testillano et al 2004) microspore embryogenesis. High frequencies of spontaneous doubling in cereals appear to be induced by treatments that block cell wall formation during the first cell divisions (Shim et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Kasha et al (2001) demonstrated that nuclear fusion leads to chromosome doubling during mannitol pretreatment of barley (Hordeum vulgare L.) microspores. With the present protocol the number of divisions increased and microspores were in a better physiological stage.…”
Section: Immonen and Robinsonmentioning
confidence: 99%
“…Androgenesis is a process of embryos development without fertilisation, from microspores, following a treatment with exogenous stress. As a result, after spontaneous or induced diploidization, completely homozygous plants -doubled haploids (DH) are obtained (Kasha et al 2001). Androgenesis may be performed using two approaches: anther culture (AC) which is labour-intensive but applied more extensively, and a more technologically advanced method by isolated microspore culture (IMC).…”
mentioning
confidence: 99%